The role of proteasome activators PA28αβ and PA200 in brown adipocyte differentiation and function - Koçberber, Zeynep; Willemsen, Nienke; Bartelt, Alexander (Frontiers in Endocrinology, 2023)
Brown adipocytes produce heat through non shivering thermogenesis (NST). To adapt to temperature cues, they possess a remarkably dynamic metabolism and undergo substantial cellular remodeling. The proteasome plays a central role in proteostasis and adaptive proteasome activity is required for sustained NST. Proteasome activators (PAs) are a class of proteasome regulators but the role of PAs in brown adipocytes is unknown. Here, we studied the roles of PA28α (encoded by Psme1) and PA200 (encoded by Psme4) in brown adipocyte differentiation and function. We found that Psme1 and Psme4 are expressed in brown adipocytes in vivo and in vitro. Through silencing of Psme1 and/or Psme4 expression in cultured brown adipocytes, we found that loss of PAs did not impair proteasome assembly or activity, and that PAs were not required for proteostasis in this model. Loss of Psme1 and/or Psme4 did not impair brown adipocyte development or activation, suggesting that PAs are neither required for brown adipogenesis nor NST. In summary, we found no role for Psme1 and Psme4 in brown adipocyte proteostasis, differentiation, or function. These findings contribute to our basic understanding of proteasome biology and the roles of proteasome activators in brown adipocytes.